"Wholly Aflame": Erotic Asceticism in the Work of Sara Maitland - Fisk, Anna (Theology & sexuality, 2010)
The writing of the Christian feminist novelist Sara Maitland has explored the interplay of eroticism, masochism and asceticism in women's spirituality. Maitland's 1984 novel Virgin Territory and 1987 essay "Passionate Prayer: Masochistic Images in Women's Experience" condemns how, in patriarchal Christianity, a model of romantic relationship with God, when compounded by the symbolism of women's sinfulness, results in spiritual masochism for women. In her later work, Maitland's writing takes a more ambivalent attitude, wanting to preserve the "otherness" of historical women mystics and martyrs, also admiring the "purity" of the extremity of their devotion. This reflects Maitland's advocating of an excessive and "unsafe" spirituality, given representation in her fiction and in her pursuit of a solitary lifestyle, as explained in 2008's A Book of Silence.